2022
DOI: 10.3390/ijgi11010039
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Route Planning Method of Connected Vehicles for Improving the Transport Efficiency

Abstract: In recent years, the route-planning problem has gained increased interest due to the development of intelligent transportation systems (ITSs) and increasing traffic congestion especially in urban areas. An independent route-planning strategy for each in-vehicle terminal improves its individual travel efficiency. However, individual optimal routes pursue the maximization of individual benefit and may contradict the global benefit, thereby reducing the overall transport efficiency of the road network. To improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has better convergence ability compared to other algorithms. Liu et al [8] innovatively introduced a bidding mechanism in the scenario of connected vehicles and proposed a new dynamic route-planning method. Experiments showed that in large-scale traffic flow scenarios, the bidding mechanism was beneficial for improving the transportation efficiency of the road network.…”
Section: Related Work and Limitationmentioning
confidence: 99%
See 3 more Smart Citations
“…It has better convergence ability compared to other algorithms. Liu et al [8] innovatively introduced a bidding mechanism in the scenario of connected vehicles and proposed a new dynamic route-planning method. Experiments showed that in large-scale traffic flow scenarios, the bidding mechanism was beneficial for improving the transportation efficiency of the road network.…”
Section: Related Work and Limitationmentioning
confidence: 99%
“…Reference [7] also optimizes and improves the algorithm to improve its convergence performance, which is different from the goal of the method we constructed. Reference [8] is mainly aimed at optimizing the transportation efficiency of the road network and improving the transportation capacity of vehicles. Our method has different research objectives, aiming to match tourist interests and reduce travel costs.…”
Section: The Difference and Advantage Of Our Proposed Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the complexity is high. Furthermore, to increase travel efficiency, a dynamic route planning method 34 was proposed. This approach uses a local search algorithm to choose the route in large‐scale traffic conditions.…”
Section: Literature Reviewmentioning
confidence: 99%